Birth outcomes of cases with different congenital heart defects - a population-based study - Vereczkey, Attila; Gerencsér, Balázs; Czeizel, Andrew E; Szabó, István (International Journal of Health, 2015)
Background: In general, previous epidemiological studies evaluated congenital heart defects (CHDs) together. The aim of the present study was to identify possible etiological factors of different CHD-entities, because the underlying causes are unclear in the vast majority of patients.Objectives: Different CHD-entities as homogeneously as possible with confirmed diagnoses were analyzed in the population-based large dataset of the Hungarian Case-Control Surveillance of Congenital Abnormalities.Methods: 3,750 live-born singleton CHD-patients were analyzed according to birth outcomes, i.e. gestational age at delivery and birth weight, the rate of preterm birth, low birthweight and small for gestational age.Results: The major findings of the study showed that cases with different CHD-entities had shorter gestational age at delivery and lower mean birth weight, and these variables associated with a higher rate of preterm birth and particularly with a much higher rate of low birthweight and small for gestational age. This study showed the importance of sex in the birth outcomes of some CHD-entities. The question is why several CHD-entities manifested more frequently in newborns with intrauterine growth restriction because fetal heart has a passive role before birth without pulmonary circulation.Conclusions: The birth outcomes of cases indicate the effect of CHDs for fetal development. In addition maternal confounders have to consider. Finally, CHDs and intrauterine growth restriction as two developmental errors may have a common route, thus fetal growth and birthweight associated gene polymorphisms may have a role in the origin of CHDs.